Rabbit’s Gastrointestinal Helminthiasis: Identification And Correlation with Age, Sex and Hygiene - Indrasanti, Diana; Indradji, Mohandas; Yuwono, Endro; Ulfah, Annistia Rahmadian (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
The growing demand for high-protein low-fat meat has encouraged the development of potential rabbit farming. One of the obstacles in the rabbit farming is a disease. The studies of gastrointestinal helminthiasis in rabbits are limited, especially in Indonesia. The study aimed to identify and determine the prevalence of helmith infestation, and investigate the correlation between age, sex, and hygiene with the occurrence of gastrointestinal helminthiasis in small-scale rabbit farms. The survey was conducted on 476 rabbits in Banyumas District using a purposive sampling to collect fecal samples and questionnaire data. Both male and female rabbits were devided into four age groups: wean 1 (birth-1 month), wean 2 (>1-6 months), young (>6-18 months), and adult (>19 months). The feces were examined using the floating and the Whitlock methods and gastrointestinal helminthiasis were identified by observing the morphology of eggs and gastrointestinal helmiths. Data were subject to descriptive analysis and logistic regression using JASP software 0.16.3 version. The results demonstrated that 50 rabbits (10.50%) were infested with nematode and cestode worms. Nematode eggs found in rabbit feces in this study were strongyle (33.33%), Trichostrongylus (27.78%), Cittotaenia (14.81%), Passalurus (12.96%), Trichuris (7.41%), Hymenolepis (1.85%), Toxocara (1.85%) and Strongyloides (1.85%). The most prevalent egg worm in rabbits was Strongyle (33.33%) and lowest were Hymenolepis, Toxocara and Strongyloides (1.85% each). This study revealed that age and sex had no effect on the prevalence of gastrointestinal helminthiasis in rabbits (p>0.05). The frequency and technique of cage cleaning had a highly significant (p<0.01) effect on the occurence of gastrointestinal helminthiasis in rabbits, however there was no significant link with the separation of feces and urine in the cage (p>0.05).It can be inferred that the prevalence of gastrointestinal helminthiasis in rabbits is relatively low, and the management system including the hygiene of the cage are the most important factors in preventing its emergence.